Discrete Time Averaging of Non-Ideal PWM DC-DC Converters Operating in DCM with Feedback (Global Journals of Research in Engineering, 2013)
This paper presents a one-cycle-average (OCA) discrete-time model for PWM switched dc-dc converters operating in discontinuous conduction mode (DCM). The closed-loop system is considered in the presence of circuit parasitic. This model provides the exact OCA values of the output voltage and inductor current considering the conduction losses in the switching stage components. It also provides the exact discrete-time mathematical representation of the average values of other internal signals with little increase in simulation time. It is compared to some existing averaged models in terms of accuracy and speed through simulation results of boost converter.
Keywords: Simulation compared